2000
DOI: 10.1021/bi991974a
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Copper Binding Site on the Spinach Cytochromeb6fComplex:  Implications for QoSite Catalysis

Abstract: The isolated cytochrome (cyt) b(6)f complex from spinach is inhibited by Cu(2+) with a K(D) of about 1 microM at pH 7.6 in the presence of 1.6 microM decyl-plastoquinol (C(10)-PQH(2)) as a substrate. Inhibition was competitive with respect to C(10)-PQH(2) but noncompetitive with respect to horse heart cyt c or plastocyanin (PC). Inhibition was also pH-sensitive, with an apparent pK at about 7, above which inhibition was stronger, suggesting that binding occurred at or near a protonatable amino acid residue. Eq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(3 citation statements)
references
References 72 publications
0
3
0
Order By: Relevance
“…Typically, those interactions are examined using EPR spectroscopy with which distances between paramagnetic centers up to about 7 nm can be determined (2838). Examples of the pairs of the redox centers for which distances were measured include the heme b −3Fe4S cluster of complex II (28), tyrosine radical−nonheme Fe(II) of PSII (31), tyrosine radical−Mn cluster of PSII (39), Cu A −heme a of cytochrome oxidase (30), Cu 2+ −heme of cytochrome f in cytochrome b 6 f (37), and cytochrome c /cytochrome oxidase (in this case estimation of distance distribution in the interprotein complex was reported (38)). In the case of cytochrome bc 1 , early EPR examination of mitochondrial enzyme allowed to approximate a spatial organization of its redox active centers revealing existence of weak spin−spin interactions between the FeS center, heme b 566 ( b L ), and heme c 1 (40).…”
mentioning
confidence: 99%
“…Typically, those interactions are examined using EPR spectroscopy with which distances between paramagnetic centers up to about 7 nm can be determined (2838). Examples of the pairs of the redox centers for which distances were measured include the heme b −3Fe4S cluster of complex II (28), tyrosine radical−nonheme Fe(II) of PSII (31), tyrosine radical−Mn cluster of PSII (39), Cu A −heme a of cytochrome oxidase (30), Cu 2+ −heme of cytochrome f in cytochrome b 6 f (37), and cytochrome c /cytochrome oxidase (in this case estimation of distance distribution in the interprotein complex was reported (38)). In the case of cytochrome bc 1 , early EPR examination of mitochondrial enzyme allowed to approximate a spatial organization of its redox active centers revealing existence of weak spin−spin interactions between the FeS center, heme b 566 ( b L ), and heme c 1 (40).…”
mentioning
confidence: 99%
“…In particular, the electron transverse relaxation, T M , of SQ in the bacterial protein is strongly enhanced by the heme cofactors. [10a] This paramagnetic relaxation enhancement (PRE) was examined in detail in the mitochondrial cyt bc 1 because PRE is useful for measuring distances between spins in proteins [18] including the Fe 2 S 2 -heme b L distance in cyt bc 1 by Sarewicz et al, [19] copper ion bound to cyt b 6 f , [20] cyt c bound to cyt c oxidase, [21] and spin-labeled metmyoglobin. [22] …”
Section: Resultsmentioning
confidence: 99%
“…These experiments clearly demonstrated that the cytochrome b 6 f ISP from this complex undergoes large conformational shifts in response to changes in occupancy of the Q o site, providing the first strong support for such conformational changes in cytochrome b 6 f catalysis. The second advance has come from our demonstration that Cu 2+ inhibits the cytochrome b 6 f complex, probably by interfering with ISP domain movements [7,8]. We have since shown that, indeed, metal ions interfere with ISP domain movements [9].…”
mentioning
confidence: 99%